2016
DOI: 10.1007/s13277-016-4903-7
|View full text |Cite
|
Sign up to set email alerts
|

miR-15a and miR-24-1 as putative prognostic microRNA signatures for pediatric pilocytic astrocytomas and ependymomas

Abstract: In the current setting, we attempted to verify and validate miRNA candidates relevant to pediatric primary brain tumor progression and outcome, in order to provide data regarding the identification of novel prognostic biomarkers. Overall, 26 resected brain tumors were studied from children diagnosed with pilocytic astrocytomas (PAs) (n = 19) and ependymomas (EPs) (n = 7). As controls, deceased children who underwent autopsy and were not present with any brain malignancy were used. The experimental approach inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
2
21
2
Order By: Relevance
“…Costa et al identified over expression of miR‐203 as an independent marker for relapse . In a recent study, miR‐15a and miR‐24‐1 were found upregulated in ependymoma associated with inferior prognosis . These miRs were not identified in our study.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…Costa et al identified over expression of miR‐203 as an independent marker for relapse . In a recent study, miR‐15a and miR‐24‐1 were found upregulated in ependymoma associated with inferior prognosis . These miRs were not identified in our study.…”
Section: Discussioncontrasting
confidence: 71%
“…12 In a recent study, miR-15a and miR-24-1 were found upregulated in ependymoma associated with inferior prognosis. 13 These miRs were not identified in our study. This may be due to the difference in the comparison groups.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Thus, identification of miRNA-mRNA pairs and discovering the regulation network may potentially uncover useful cancer biomarkers. Recent research has revealed miR-15a and miR-24-1 are up-regulated in EPNs relapsed and deceased cases when compared to both the clinical remission cases and survivors, and may serve as a candidate of inferior prognostic molecules in children with EPNs (Braoudaki et al, 2016). As important regulators of life activities, miRNAs are closely related to cancer (Hayes et al, 2014) through its altered expression levels that affect the content of downstream genes (Esquela-Kerscher and Slack, 2006).…”
Section: Introductionmentioning
confidence: 99%